Peranan Orang Tua dalam Pembentuk Moral Anak - Jeni Nopilana (Indonesian Publication Center, 2025)
The life of every human being must go through a period of development which includes social, cognitive, interest and moral aspects, starting from infancy, childhood, adolescence and old age. Along with this development, the role of the family environment greatly determines whether or not a child reaches this stage of development. Because the family is the first and foremost education for children, especially in forming the basics of their personality. This research examines